2012
DOI: 10.1371/journal.pone.0038998
|View full text |Cite
|
Sign up to set email alerts
|

Three Linked Vasculopathic Processes Characterize Kawasaki Disease: A Light and Transmission Electron Microscopic Study

Abstract: BackgroundKawasaki disease is recognized as the most common cause of acquired heart disease in children in the developed world. Clinical, epidemiologic, and pathologic evidence supports an infectious agent, likely entering through the lung. Pathologic studies proposing an acute coronary arteritis followed by healing fail to account for the complex vasculopathy and clinical course.Methodology/Principal FindingsSpecimens from 32 autopsies, 8 cardiac transplants, and an excised coronary aneurysm were studied by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
334
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(357 citation statements)
references
References 61 publications
(69 reference statements)
18
334
0
5
Order By: Relevance
“…from autopsies of young adult KD patients has been demonstrated by immunohistochemistry [6]. Myofibroblasts in KD patients may remain activated and cause progressive luminal narrowing of coronary artery to the point of total occlusion [33]. In the present study, we demonstrated expression of Gal-3 in SMA-expressing spindle-shaped cells in myocardium.…”
Section: Discussionsupporting
confidence: 62%
“…from autopsies of young adult KD patients has been demonstrated by immunohistochemistry [6]. Myofibroblasts in KD patients may remain activated and cause progressive luminal narrowing of coronary artery to the point of total occlusion [33]. In the present study, we demonstrated expression of Gal-3 in SMA-expressing spindle-shaped cells in myocardium.…”
Section: Discussionsupporting
confidence: 62%
“…73,131 Common sites include the axillary, subclavian, brachial, femoral, iliac, splanchnic, and mesenteric arteries, usually near or at branching points. These may present clinically as pulsatile masses and bruits.…”
Section: Other Arterial Abnormalitiesmentioning
confidence: 99%
“…Myocarditis in KD likely improves rapidly as the inflammatory process subsides because it results from interstitial edema and inflammation and only rarely from myocardial cell necrosis. 73,122 Infrequently, acute myocardial inflammation is associated with overt ventricular ectopy, although recent information indicates more common repolarization impact than may be clinically apparent (see Long-Term Management, Arrhythmias). The exception to the more typical short-term impact of mild myocarditis in KD is the KD shock syndrome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that inflammatory cytokines are essential factors for the pathogenesis of inflammation in Kawasaki disease and that coronary artery lesions were caused by abnormal activation of endothelial cells, progressive injury of the arterial media and activation/ disruption of the coagulation and fibrinolysis systems [27,28].…”
Section: Plasma Exchangementioning
confidence: 99%